SUSPENDAREA ACTELOR ADMINISTRATIVE - Diaconu, Mihail (SUPREMANCE OF LAW, 2018)
The article includes an analysis of the issue of suspension as a means of sanctioning the unlawfulness of administrative acts. The emphasis is placed on the essence of this measure and its particularities exposed in doctrine, the author coming up with clarifications and comments.
Keywords: administrative act; legality; opportunity; administrative control; sanction; revocation; suspension; cancellation